Antecedents of Financing on Indonesian Islamic Banks - Ayatullah Adi Sasono; Osama Alhendi (Business, Accounting and Management Journal, 2023)
The purpose of this study is to analyze the impact of capital, profitability, efficiency, funding risk, liquidity, inflation, and BI rates on funding. The population used in this study consists of Indonesian Islamic banks listed on the Indonesia Stock Exchange. Descriptive statistics, classical hypothesis testing, multiple  regression analysis, and hypothesis testing were used to analyze the data. The samples were determined using targeted sampling, so 52 samples were included in this study. The research results show that capital variables do not have a significant impact on financing, profitability does not have a significant impact on financing, efficiency does not have a significant impact on financing, and financing risk has a significant impact on financing. However, liquidity does not have a significant impact on funding.